La animación a la lectura incide en el aprendizaje de los niños de tercer grado de la Unidad Educativa Holger Montenegro Molina de Buena Fe Provincia de Los Ríos, año 2020 - Moreira Cedeño, Maira María (2021)
The following research project has sought an answer to the question of whether children who have an animation or predisposition to reading also have better learning within the project, it has been found that many children mainly do not have a motivation to read so An answer has been sought on the null motivation and predisposition that children have. Through surveys with yes and no answers, teachers and parents have evaluated the children's motivation to read and how it is reflected in their academic development. It has been found through surveys that according to teachers the educational system has shortcomings when it comes to motivating children and that parents do not fulfill a pedagogical role that they should have, delegating all responsibility to the educational system. Finally, it has also been inferred that the problem of low motivation and how it affects learning is not only of the educational establishment to study but is something generalized at the national educational level.